Consecuencias psicológicas del confinamiento por covid 19 en integrantes de la comunidad educativa I.E.I. № 369 San Isidro, Ramón Castilla Loreto 2021 - Medina Usuriaga, Cynthia Pilar (2023)
The interest in conducting this research was based on the purpose of describing the psychological consequences of confinement due to covid 19 in members of the I.E.I. № 369 in the community of San Isidro, province of Ramón Castilla, Loreto region in the year 2021. For this purpose, the type of descriptive research was used as a methodology through a univariate, cross-sectional, and field design. The population determined for the population was made up of the members of the educational community, directors, teachers and parents, which was 59 people, and the sample was census, because they were all considered. To obtain the data, it was necessary to consider the survey technique and as an instrument a questionnaire was used that was validated by experts before proceeding with the collection. The most relevant conclusion was that the psychological consequences in the members of the educational community I.E.I № 369 of San Isidro was low in 33.9%, moderate in 49.2% and high in 16.9%.